Potensi Pemanfaatan Burung Hantu Sebagai Pengendalian Tikus Sawah di Desa Bener, Kecamatan Wonosari Kabupaten Klaten - Dhika Kintania Primadani; Bonjok Istiaji; Swastiko Priyambodo; Anna Ardillah Sanmas; Nadia Fauzana; Titah Nurhawati; Ainur Rosidah; Arda Ardella; Dyas Almira Rahmadhani; Indah Sukmawati; Lufi Diah Pratiwii (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Rat is important pest especially in rice field. This program aims to find out effectiveness of using owl as biological control of rice field rat and compare them with other controls. The program is located in Bener village, Wonosari, Klaten. The method of the program are interview and observation. The result showed that the application of owl has not been use optimally. Making owl nest box that’s not according to the standard make owl reluctant to the owl nest that has been made. In addition, there is lack of public awareness of synchronously control, so it makes rat’s attack increase. Control of rat does not rely on owl as its predator, but it’s also combined with other controls like gropyokan, emposan, and toxic bait synchronously and continuously so it can achieve success in decreasing of development rice field rat. Keywords: owl, owl nest box, rice field rats